2018
DOI: 10.2478/pjph-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among students of medical universities in Poland

Abstract: Introduction. Burnout among medical students have been thoroughly studied in a number of countries worldwide. Little is known about medical students burnout in the Central European countries. Material and methods. The study is based on the Copenhagen Burnout Inventory, adapted for measurement of burnout among medical students. The questionnaire contained 6 numerical scale questions about respondents’ satisfaction with studies, university and educational achievements. Students of Polish medical universities wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(26 reference statements)
1
4
0
Order By: Relevance
“…Our study revealed that most of the students did not smoke at all (69.40%), and only 16.67% of them were current smokers who consumed, on average, 7.77 ± 6.38 cigarettes in a day. These results are like those identified by other studies on medical students such as El Ansari et al [70], Zarobkiewicz et al [71], or Niu et al [72]. Some other studies showed that about a quarter of all U.S. students smoked [73], and 75% of them continued to smoke in adulthood [74], placing future adults at greater risk of developing lung cancer and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study revealed that most of the students did not smoke at all (69.40%), and only 16.67% of them were current smokers who consumed, on average, 7.77 ± 6.38 cigarettes in a day. These results are like those identified by other studies on medical students such as El Ansari et al [70], Zarobkiewicz et al [71], or Niu et al [72]. Some other studies showed that about a quarter of all U.S. students smoked [73], and 75% of them continued to smoke in adulthood [74], placing future adults at greater risk of developing lung cancer and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, they internalise the information they gather, and our results showed that some selfdestructive behaviours, such as smoking, decrease during university studies. [39,71,72] Smoking decreased from the first to the sixth year of medical studies, and regarding physical activity, scores were significantly higher for first-year students compared to sixth year's students, suggesting that older students had a more sedentary lifestyle [39,40,80]. The relationship between physical activity, sleep quality, and health-related quality-of-life was pointed out also by Izawa et al [81,82].…”
Section: Discussionmentioning
confidence: 94%
“…For example, items, such as “Is your work emotionally exhausting,” were modified to “Is your university work emotionally exhausting.” For this study, the subscale of “Client-related burnout” within the CBI was not used as it was deemed irrelevant to the focus of the research. The CBI has been adapted to be used with students before [ Campos et al, 2013 (Portugal/Brazil), Sveinsdóttir et al, 2021 (Iceland, nursing students), and Zarobkiewicz et al, 2018 (Poland, medical students)]. For both personal and academic burnout, an average percentage score was calculated, which could range from 0 to 100%, with higher scores indicating a higher degree of burnout.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above, the authors made a questionnaire with three subscales focusing on the individual aspects of the burnout syndrome, and highlighted the correlation between the burnout syndrome and physical exhaustion, insomnia, alcohol and drug use and various kinds of relationship problems (Maslach, Jackson, 1981). Although the beginnings of the burnout syndrome analysis are associated mainly with the performance of helping professions, it can also be noticed in the performance of other social roles, for example, it can be connected with college study (Shin, 2011, Dyrbye et al, 2009Hernesniemi et al, 2017;Kuittinen a Meriläinen, 2011;Zarobkiewicz, et al, 2018, Nikodijević, Labrović, Doković, 2012Stein, Sibanda, 2016;Ried, et al 2006, Merino-Tejedor. et al, 2015, Aghajari et al, 2018.…”
Section: Alina Budniakmentioning
confidence: 99%